Cu/ZnO/Al2O3 Catalysts Modified by Octa-Potassium Titanate Whiskers with Ultrasonic Treatment for Methanol Synthesis - Li1, Haoyuan; Wei1, Ping; Wang2, Jianqiang; Tang1, Shigui; Guo2, Cheng (Asian Journal of Chemistry, 2013)
Cu/ZnO/Al2O3/K2Ti8O17 catalysts were prepared via ultrasonic treatment by co-precipitation and their catalytic performance in methanol synthesis was evaluated in a fixed-bed reactor. The results showed that the copper-based catalysts modified with the addition of 3 wt % octa-potassium titanate at an ultrasonic frequency of 40 kHz and a power of 400 W had a remarkable effect in methanol synthesis in comparison with conventional ternary Cu/ZnO/Al2O3 catalysts. By using X-ray diffraction and nitrogen adsorption isotherms, it was found that ultrasonic treatment during co-precipitation improved the dispersion of the modified catalysts, which resulted in higher specific surface areas, larger pore structures and smaller CuO crystal sizes. In addition, high-temperature carbonates were observed in the calcined catalyst with a Cu/Zn atomic ratio of 2.2 using XRD and differential thermal analysis, indicating that ultrasonic treatment strengthened the synergistic effect between precursors and additive. The heat-resistant effect of K2Ti8O17 resulted in the remainder of a small amount of residual carbonate grains, which could enhance the catalytic activity.